Political parties and the quality of democracy in a context of changes in the party system in Costa Rica - Hernández Naranjo, Gerardo (2012)
The paper presents some preliminary reflections on the relationship between political parties and the quality of democracy in the procedural scope. It begins with an overview of the context of changes in the party system, and then raises some weaknesses of political parties in the current historical context, both in performance within the political system and their internal dynamics. The background assumption is that such weaknesses somehow affect the quality of the democracy, as they affect some basic citizen rights, in the context of representative democracy.